Colorectal Cancer Risk and Recommendations for Colorectal Cancer Surveillance in Adult Survivors of Childhood Cancer. Issue 5 (20th May 2023) - Shen, Katie; Farha, Natalie; Rotz, Seth; Balagamwala, Ehsan H.; Macaron, Carole; Mankaney, Gautam M.; Burke, Carol A.
Abstract : While many organizations have published guidance on the approach to colorectal cancer (CRC) screening in average-risk and certain high-risk groups, adult survivors of childhood cancer (ASCC) who have a heightened risk of CRC are rarely included as a target group for enhanced CRC surveillance. The population of ASCC continues to grow due to increasingly effective cancer therapies and improved survival. With this increased survival comes an increased risk for subsequent malignant neoplasms, including CRC. Since there is little published guidance for CRC surveillance in ASCC and limited awareness of increased CRC risk among both physicians and patients, the objectives of our paper are to review the incidence of and risk factors for colorectal neoplasia in ASCC, describe the clinical phenotypes of colorectal neoplasia in ASCC, review published surveillance strategies based on consensus-based survivorship guidelines, and outline areas for future research to optimize surveillance strategies.